Meteorological data from Lönnstorp, AWS, 2014-04-17–2025-12-31 - Lönnstorp Research Station (Swedish University of Agricultural Sciences, 2026)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Lönnstorp Research Station (2026). Meteorological data from Lönnstorp, AWS, 2014-04-17–2025-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/vToZYWAgYHuHFOTEkCHNtq4b
Keywords: Lönnstorp Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Wind speed; Wind speed; Soil temperature; Soil temperature; Incoming shortwave radiation; Incoming shortwave radiation; Air pressure; Air pressure; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap